The effect of foliar feeding with nutrients (N, K, B) and gibberellic acid on some vegetative growth indicators of Meyer lemon trees.: The effect of foliar feeding with nutrients (N, K, B) and gibberellic acid on some vegetative growth indicators of Meyer lemon trees. (Journal of Hama University, 2024)
This study was conducted in the Bahlouliyeh district of Latakia Governorate during the 2022 and 2023 agricultural seasons on lemon trees of the “Mayer” variety, 15 years old and planted at a distance of 4*4 m. In order to study the effect of foliar feeding with nutrients (N, K, B) and gibberellic acid (GA3) on some vegetative growth indicators. Four chemical compounds were used in foliar spraying: urea, potassium sulfate, boron, and gibberellic acid, individually and in combination, at different concentrations (2.5 g/l, 1.5 g/l, 200 ppm, 20 ppm), respectively. The results showed that the spraying treatment with the four compounds combined (GA3, N, B, and K) was superior to the rest of the studied treatments in tree crown size with an increase rate of (43.77%) and (43.15%) for both the first and second season, respectively, compared to the control that did not The percentage increase in tree crown size exceeds (17.84%) and (12.30%) for both seasons. The results showed that the spray treatment with the four compounds combined (GA3, N, B, K) and the spray treatment with urea + boron together outperformed the rest of the treatments studied in terms of stem circumference with an increase rate of 7.59%, 7.20%, followed by the foliar spray treatment with boron + K2SO4 with an increase rate. 6.8%. The results also showed that the spray treatment with the four compounds combined, the spray treatment with urea + boron, and the foliar spray treatment with boron + K2SO4  together outperformed the rest of the studied treatments with a total chlorophyll percentage of (64.88, 63.65, 64.39) SPAD compared to the control (58.10) SPAD..-----------------------------------------------------------------------Keywords: foliar nutrition, Meyer variety, tree crown size, stem circumference, total chlorophyll